Pro Python System Administration - Sileika, Rytis; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
As time goes on, system administrators are presented with increasingly complicated challenges. In the early days, a team of engineers might have had to look after one or two systems. These days, one engineer can administer hundreds or thousands of systems. System administrators are gradually replacing their tools with more advanced and flexible ones. One of the choices is Python. Structurally, Python is a modern, high-level language with a very clean syntax. Python comes with many built-in libraries that can make automation tasks easier. It also has extensive set of third-party libraries and a very active development community. This flexibility makes Python a good choice for a wide variety of tasks, from prototyping science applications to system maintenance and administration jobs. This book explains and shows how to apply Python scripting in practice. Unlike the majority of the Python books, it will show you how to approach and resolve real-world issues that most system administrators will come across in their careers. In this book, you will find several projects in the categories of network administration, web server administration, and monitoring and database management. In each project, we will define the problem, design the solution, and go through the more interesting implementation steps. Each project is accompanied with the source code of a fully working prototype, which you’ll be able to use immediately or adapt to your requirements and environment.
Reading and Collecting Performance Data Using SNMP -- Managing Devices Using the SOAP API -- Creating a Web Application for IP Address Accountancy -- Integrating the IP Address Application with DHCP -- Maintaining a List of Virtual Hosts in an Apache Configuration File -- Gathering and Presenting Statistical Data from Apache Log Files -- Performing Complex Searches and Reporting on Application Log Files -- A Web Site Availability Check Script for Nagios -- Management and Monitoring Subsystem -- Remote Monitoring Agents -- Statistics Gathering and Reporting -- Automatic MySQL Database Performance Tuning -- Using Amazon EC2/S3 as a Data Warehouse Solution.
Keywords: Python (Computer program language).; Software engineering; Python; Software Engineering/Programming and Operating Systems